Regime transition, uncertainty and prospects for democratization: The politics for Russia's regions in a comparative perspective - Vladimir Gel'man (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
In analyzing regime transition as an open-ended process, the paradigmatic approach of the paper provides an alternative to teleological schemes of the transition to democracy. The process of regime transition, regardless of the regime type itself, includes several stages, such as the breakdown of the ancient regime, the uncertainty of the political regime, and the installation of the new regime. The key characteristics of the uncertainty stage are the uncertain position of actors and the institution-free environment. The completion of this stage is the installation of the new regime. Looking at some of Russia's regions as case studies of regime transition, the paper aims at understanding scenarios of outcomes of uncertainty and their impact on new political regimes. The “winner takes all” scenario of outcome of uncertainty is likely to enhance the power monopoly of the dominant actor and the supremacy of informal institutions. The consequences of this scenario are the emergence of new political regimes with numerous aspects of authoritarian rule. These regimes could be relatively stable. The “elite settlement” scenario of outcome of uncertainty generally includes the sharing of powers between dominant and subordinate actors in order to limit public political contestation and establish the supremacy of informal, rather than formal, institutions. These regimes are fragile and dependent on changes in the political situation. The “struggle over the rules” scenario of outcome of uncertainty is likely to provide an institutional framework as a precondition to democratization in the sense of horizontal accountability through the institutional limitation on assertions of power. Until the institutionalization of the new regime, it still remains fragile. Democracy is not emerging from regime transition by default. Only if political competition among actors within the framework of formal institutions continues to develop, transitions to democracy may occur as a contingent outcome of conflict, or as the “lesser evil” for the actors.
Keywords: 300